Childhood traumatic brain injury; education and medical disability. Issue 3 (5th August 2014) - Nilsson, Johanna; Emanuelson, Ingrid
Abstract : Purpose: – The purpose of this paper is to describe level of education and return to school and employment among children and young adults who sustained a Traumatic brain injury (TBI) 15 years ago and to analyse the occurrence of any medical disability. Design/methodology/approach: – The study is descriptive. The authors used a questionnaire with questions covering education, employment, sick leave, insurance compensation and medical follow-up. Findings: – A total of 37 individuals, 17 (45.9 per cent) women and 20 (54.1 per cent) men, participated. Just over half (20 individuals, 54.1 per cent) were in employment, five (13.5 per cent) were unemployed and four (10.8 per cent) received disability pension. In total, 18 (48.6 per cent) individuals had received full compensation from their insurance companies, while 12 (35.3 per cent) had had their medical disability classified. A total of 12 (33.3 per cent) individuals were taking medication and five (13.9 per cent) had been followed by the health care system. The results indicate that people sustaining a TBI are less successful on the labour market than the general population, that relatively few had had their disability classified and that almost 50 per cent receive no insurance compensation. Originality/value: – There are few long-term follow-up studies on brain injuries acquired during childhood, and this study would add to the previous knowledge, as aspects of medical disability and legal compensation are included.